2018
DOI: 10.3390/md16110407
|View full text |Cite
|
Sign up to set email alerts
|

The Anemonia viridis Venom: Coupling Biochemical Purification and RNA-Seq for Translational Research

Abstract: Blue biotechnologies implement marine bio-resources for addressing practical concerns. The isolation of biologically active molecules from marine animals is one of the main ways this field develops. Strikingly, cnidaria are considered as sustainable resources for this purpose, as they possess unique cells for attack and protection, producing an articulated cocktail of bioactive substances. The Mediterranean sea anemone Anemonia viridis has been studied extensively for years. In this short review, we summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…We have reported Kunitz-type peptide libraries [ 21 , 24 , 51 ], as well as an actinoporins library of H. crispa [ 52 , 53 ] and now we have data that prove the existence of a combinatorial library of APETx-like peptides of H. magnifica . Remarkably, the proteome and/or transcriptome studies resulted in finding APETx-like peptides in sea anemones belonging to the family Actiniidae, such as A. viridis [ 54 ], Anemonia sulcata [ 55 ], Cnidopus japonicus [ 56 ], A . elegantissima [ 57 ], and Bunodosoma granulifera [ 58 ], but not in sea anemones from Stichodactylidae family, such as Stichodactyla haddoni [ 59 ], Stichodactyla duerdeni [ 60 ], and Stichodactyla helianthus [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported Kunitz-type peptide libraries [ 21 , 24 , 51 ], as well as an actinoporins library of H. crispa [ 52 , 53 ] and now we have data that prove the existence of a combinatorial library of APETx-like peptides of H. magnifica . Remarkably, the proteome and/or transcriptome studies resulted in finding APETx-like peptides in sea anemones belonging to the family Actiniidae, such as A. viridis [ 54 ], Anemonia sulcata [ 55 ], Cnidopus japonicus [ 56 ], A . elegantissima [ 57 ], and Bunodosoma granulifera [ 58 ], but not in sea anemones from Stichodactylidae family, such as Stichodactyla haddoni [ 59 ], Stichodactyla duerdeni [ 60 ], and Stichodactyla helianthus [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sea anemones, Kunitz is classified as a type II K + channel inhibitor. It protects the organisms from endogenous proteases, causes paralysis in prey, and defends against enemies [ 63 , 64 ]. Molecular phylogenetic analysis of Kunitz showed that myxozoans and free-living cnidarians are clustered into distinct clades.…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is quite clear that the wide range of modulating action of NaTxs and the effect on the action potential duration of Na V s are due to their structural characteristics, surface electrostatic potential, and dipole moment [ 81 , 87 ]. Sodium channel toxins produced by sea anemones, neurotoxins, are currently the best characterized [ 1 , 2 , 4 , 7 , 13 , 14 , 22 , 35 , 37 , 39 , 58 , 80 , 88 , 89 ]. Traditionally all NaTxs studied to date have been classified into four structural types, according to amino acid sequences and a different Cys residues distribution pattern ( Figure 2 , Figure 3 , Figure 4 and Figure 5 ) [ 2 , 7 , 80 , 81 , 90 ].…”
Section: Structure-functional Characteristics Of Sea Anemone Natxsmentioning
confidence: 99%
“…Today, more than 40 type 1 NaTxs are known ( Figure 2 ); most of them have been isolated from the species belonging to the Actiniidae family (Anthopleura, Anemonia, Condylactis, Bunodosoma, Actinia, Antheopsis genera) [ 2 , 81 ]. Besides several A. equina neurotoxins, some amino acid sequences of putative homologs of the native neurotoxin Av2 have been derived from the sea anemone A. viridis gDNA sequence [ 88 , 95 ]. Gene cloning, which became a traditional method of studying sea anemone neurotoxins by the end of the last century, made it possible to detect up to a dozen or even more highly homologous amino acid sequences in each of the studied species, which significantly expanded the arsenal of neurotoxins for further structural and functional studies [ 5 , 14 , 16 , 39 ].…”
Section: Structure-functional Characteristics Of Sea Anemone Natxsmentioning
confidence: 99%